Sedimentological and paleontological anaylsis of a profile from Lake Ohrid - Wagner, Bernd; Lotter, André F; Nowaczyk, Norbert R; Reed, Jane M; Schwalb, Antje; Sulpizio, Roberto; Valsecchi, Verushka; Wessels, Martin; Zanchetta, Giovanni (Supplement to: Wagner, B et al. (2009): A 40,000-year record of environmental change from ancient Lake Ohrid (Albania and Macedonia). Journal of Paleolimnology, 41, 407-430, https://doi.org/10.1007/s10933-008-9234-2, 2009)
Lake Ohrid is considered to be of Pliocene origin and is the oldest extant lake in Europe. A 1,075- cm-long sediment core was recovered from the southeastern part of the lake, from a water depth of 105 m. The core was investigated using geophysical, granulometric, biogeochemical, diatom, ostracod, and pollen analyses. Tephrochronology and AMS radiocarbon dating of plant macrofossils reveals that the sediment sequence spans the past ca. 39,500 years and features a hiatus between ca. 14,600 and 9,400 cal. year BP. The Pleistocene sequence indicates relatively stable and cold conditions, with steppe vegetation in the catchment, at least partial winter ice-cover of the lake, and oxygenated bottom waters at the coring site. The Holocene sequence indicates that the catchment vegetation had changed to forest dominated by pine and summer-green oak. Several of the proxies suggest the impact of abrupt climate oscillations such as the 8.2 or 4.0 ka event. The observed changes, however, cannot be related clearly to a change in temperature or humidity. Human impact started about 5,000 cal. year BP and increased significantly during the past 2,400 years. Water column mixing conditions, inflow from subaquatic springs, and human impact are the most important parameters influencing internal lake processes, notably affecting the composition and characteristics of the sediments.